Proceedings of the 25th Annual ACM Symposium on User Interface Software and Technology 2012
DOI: 10.1145/2380116.2380174
|View full text |Cite
|
Sign up to set email alerts
|

Designing for low-latency direct-touch input

Abstract: Software designed for direct-touch interfaces often utilize a metaphor of direct physical manipulation of pseudo "realworld" objects. However, current touch systems typically take 50-200ms to update the display in response to a physical touch action. Utilizing a high performance touch demonstrator, subjects were able to experience touch latencies ranging from current levels down to about 1ms. Our tests show that users greatly prefer lower latencies, and noticeable improvement continued well below 10ms. This le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
124
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 162 publications
(127 citation statements)
references
References 22 publications
3
124
0
Order By: Relevance
“…This end-to-end latency can be split into hardware latency (on input side: sensing, transmission and on output side : display) and software latency (system, toolkits, frameworks and applications). End-to-end latency is still affecting most interactive systems [9,27,30], from desktop computers (where latency is between 50 and 90 ms [9]) to touch-based devices (typically, latency on touch-screens is between 60 and 200 ms [10,30]). And while modern input controllers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This end-to-end latency can be split into hardware latency (on input side: sensing, transmission and on output side : display) and software latency (system, toolkits, frameworks and applications). End-to-end latency is still affecting most interactive systems [9,27,30], from desktop computers (where latency is between 50 and 90 ms [9]) to touch-based devices (typically, latency on touch-screens is between 60 and 200 ms [10,30]). And while modern input controllers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In OST systems, the real world is viewed directly, which makes the latency detectable at considerably lower levels. A study by Ng et al [29] found the JND of latency to be as low as 2.38 ms for OST systems.…”
Section: Latency Detectionmentioning
confidence: 97%
“…They achieved a latency of only 200µs, though the memory limitations of their platform permitted parallax in only one dimension. The closest example to ours is that of Ng et al [9], who built a low latency direct touch interaction interface. They also designed theirs for latency interaction experiments.…”
Section: Related Workmentioning
confidence: 99%
“…FPGAs have been used for real-time rendering before, but with limited scope and tight vertical integration (e.g. [8], [9]). The dataflow computing paradigm and tools such as Maxeler's MaxCompiler are making it possible to construct image generators with entirely novel architectures, with similar complexity of programming as traditional GPUs [10].…”
Section: Introductionmentioning
confidence: 99%